Design of Information Terminal for Train Passenger Information System - ZHANG Ling-yun; CUI Li-ling (机车电传动)
Information terminal of train passenger information system were introduced from structure, configuration, functions and etc, and its working principle and importance in urban mass transportation was explained. With test and operation evaluating, it was proved completely meet the requirements of the purchaser with superior performance.